Reconciliation and Healing as a Paradigm for Mission - Schreiter, Robert J. (International review of mission, 2005)
Recent years have witnessed a discussion about reconciliation an? healing as providing a new paradigm for mission. This article looks at the use of paradigms as a way to understand missionary history and activity, and explores paradigms that emerged in the second half of the 20th century. It then turns to how reconciliation and healing are being understood today, and how they might provide both a model of, and a model for, mission.